2011
DOI: 10.4103/0974-7753.90823
|View full text |Cite
|
Sign up to set email alerts
|

Trichorrhexis nodosa with nail dystrophy: Diagnosis by dermoscopy

Abstract: A 25-year-old male, born of non-consanguineous marriage presented with complaints of sparse and thin hairs over scalp and dystrophy of nails since childhood. This case highlights the association of trichorrhexis nodosa with nail dystrophy and the use of trichoscopy as a noninvasive method for diagnosis of hair disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“… 4 - 6 This method also allows diagnosing other hair shaft genetic dystrophies, such as monilethrix, trichorrhexis nodosa, pili torti, pili annulati . 5 - 8 Electronic microscopy studies suggest that TI occurs due to a transient defect in the keratinization in the inner root sheath, which is keratinized but the hair shaft is not. It is suggested that the weakness in the hair cortical region arises from the incomplete sulfhydryl conversion into sulfide bridges in the cortical region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 - 6 This method also allows diagnosing other hair shaft genetic dystrophies, such as monilethrix, trichorrhexis nodosa, pili torti, pili annulati . 5 - 8 Electronic microscopy studies suggest that TI occurs due to a transient defect in the keratinization in the inner root sheath, which is keratinized but the hair shaft is not. It is suggested that the weakness in the hair cortical region arises from the incomplete sulfhydryl conversion into sulfide bridges in the cortical region.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 In recent years the application of trichoscopy has increased for diagnosing cicatricial and noncicatricial alopecias, inflammatory diseases and scalp hair shaft disorders such as monilethrix, trichorrhexis nodosa, pili torti, pili annulati and TI. 4 - 8 …”
Section: Introductionmentioning
confidence: 99%